Exploring cultural values in conflict management: a qualitative study of university heads of departments - Akanji, Babatunde; Mordi, Chima; Ajonbadi, Hakeem; Adekoya, Olatunji David (Qualitative research in organizations and management, 2021)
PurposeIn seeking to understand the impact of culture on conflict management (CM), extant organisational management research has, for the most part, confined itself to using the one-dimensional collectivism/individualism model of Hofstede's cultural theory. The purpose of this present study is to extend this knowledge area by adopting the more comprehensive analysis of Hofstede's fourfold dimensional typology – power distance, individualism/collectivism, uncertainty avoidance and masculinity/femininity – as a conceptual lens to investigate how national culture impacts the interpersonal CM of those in leadership positions in higher education institutions. Specifically, this article explores the extent to which cultural values influence the CM practices of university heads of departments (HODs).Design/methodology/approachAdopting a qualitative approach, 36 interviews were conducted with heads of different departments across a variety of disciplines in selected Nigerian universities.FindingsThe study's results conceptualise how underlying cultural norms – promoting paternalism, servility and social relations – influence the conflict-handling strategies adopted by university HODs. It consequently emerged from the thematic analysis that in Nigeria, conflict-handling decisions are shaped by status-based dictates, a normative emphasis on communality, masculine hegemony and religious motivation – as opposed to Western cultures, where these benevolent and integrative values play a far smaller role.Research limitations/implicationsThe study focussed on a small group of research subjects. Although the sample is not a sample that enables generalisation, the findings provide theoretical insights into how cultural ascendancy could frame conflict resolutions. This research is especially relevant as it runs in a culture significantly different from the ones that originally were investigated and in which managerial books and mainstream practices emerged and, thus, can contribute to challenge and enhance theory.Originality/valueThe study seeks to advance knowledge of the interface between culture and CM in a sub-Saharan African context where literature is scarce.